Pengaruh Iklim Komunikasi terhadap Engagement Karyawan - Ni Nengah Dwi Hendrawati; Arintowati H Handoyo; Poppy Ruliana; Irwansyah Irwansyah (Inter Komunika, 2018)
Abstract. The problem in this study is to find out and analyze how the communication climate affects employee engagement. The purpose of the study was to determine and analyze the influence of the communication climate dimension on employee engagement.The theory used in this study uses communication climate theory from Redding, 1972 (in Ruliana, 2016: 171), consisting of supportiveness, participative decision making, truth-confidence-credibility, openness and candor, and high performance goals.The theory used in this study uses communication climate theory (Redding, 1972 in Ruliana, 2016: 171), Employee engagement theory (Mowday, Steers & Porter, 1979 in Hayase 2009).The research method used is an explanatory survey method in the head office employee population in June 2018, with total sampling technique.  Of the total population of 262 people who responded to 226 respondents. To test the validity of the instrument, 30 respondents were used by using the Pearson Product Moment statistical formula and reliability using the Cronbach’s Alpha coefficient. 226 data were analyzed quantitatively through a simple linear regression test.Data collection techniques are carried out through field observations, questionnaires, interviews, documentation, literature studies and through the internet.The results showed the influence of the communication climate on employee engagement. Thus the theory used supports this research.Keywords: Communication Climate, Employee Engagement.Abstrak. Permasalahan dalam penelitian ini adalah untuk mengetahui dan menganalisa bagaimana iklim komunikasi mempengaruhi engagement karyawan.Tujuan penelitian adalah untuk mengetahui dan menganalisis pengaruh dimensi iklim komunikasi terhadap engagement karyawan.Teori yang digunakan dalam penelitian ini menggunakan teori iklim komunikasi dari Redding, 1972 (dalam Ruliana, 2016: 171), terdiri dari supportiveness, participative decision making, truth-confidence-credibility, openness and candor, dan high performance goals.Metode penelitian yang digunakan adalah metode survei eksplanatori pada populasi karyawan kantor pusat pada Juni 2018, dengan teknik total sampling.   Dari jumlah populasi sebanyak 262 orang yang merespon sebanyak 226 responden.  Untuk menguji validitas instrumen digunakan 30 responden dengan menggunakan rumus statistik Pearson Product Moment dan reliabilitas menggunakan koefisien  Alpha Cronbach.   Data sejumlah 226 dianalisis secara kuantitatif melalui uji regresi linear sederhana.Teknik pengumpulan data dilakukan melalui observasi lapangan, penyebaran kuesioner, wawancara, dokumentasi, studi kepustakaan serta melalui internet. Hasil penelitian menunjukkan adanya pengaruh iklim komunikasi terhadap engagement karyawan.  Dengan demikian teori yang digunakan mendukung penelitian ini.Kata kunci: iklim komunikasi , engagement  karyawan